Improved User Position Monitor for WAAS. Issue 1 (March 2017) - Walter, Todd; Blanch, Juan
Abstract: This paper describes an efficient new algorithm being developed for the Wide Area Augmentation System (WAAS) that significantly improves its ability to detect threats arising from multiple simultaneous one to two sigma errors. This new algorithm is based on the sum of the squares of the normalized errors at each reference station. It has significantly improved the ability to detect error conditions that are not obviously faulted individually, but that could be harmful to users when combined. Currently, other monitors are inflating the confidence bounds to protect against such conditions. This new User Position Monitor (UPM) is able to identify such threats, and as a consequence, excess conservatism may be removed from the system. We expect this innovation to lead to better availability while maintaining equal or better levels of integrity. Copyright © 2017 Institute of Navigation